Analysis Of Factors Affecting The Incidence Of High-Risk Pregnancies In The Working Area Of The Mubune Health Center, Northern Minahasa District - Merke Lengkong; Freddy W. Wagey; Suryadi N. N. Tatura (International Publisher, 2023)
High-risk pregnancy refers to any condition associated with pregnancy where there is an actual or potential risk to the mother or fetus. Observations in North Minahasa Regency in 2022 showed a total of 1,015 detected cases of high-risk pregnancies in Community Health Centers. Based on data, Mubune Community Health Center has the highest number of high-risk pregnancy cases, totaling 193 cases. Therefore, efforts are needed to reduce these high-risk pregnancies through this research. The research design used in this study is an observational analytic study with a cross-sectional approach. The study was conducted in the working area of Mubune Community Health Center, North Minahasa, from April to July 2023. The sample in this study consisted of all pregnant women recorded in Mubune Community Health Center, totaling 225 patients, with 82 pregnant women classified as high-risk based on the data. The research variables consist of independent variables (maternal age, maternal knowledge, and maternal attitude) and the dependent variable (occurrence of high-risk pregnancy). Data collection was done through interviews using a questionnaire. The data from this study were analyzed using univariate analysis, bivariate analysis, and multivariate analysis. The analysis results showed that there is a relationship between maternal age (p = 0.000), maternal knowledge (p = 0.007), and maternal attitude (p = 0.033) with the occurrence of high-risk pregnancy in the working area of Mubune Community Health Center, North Minahasa. The multivariate analysis results showed that the exp β value of maternal age variable in the category of <20 years and >35 years is 21.6 times the occurrence of high-risk pregnancy. Based on the Nagelkerke R-square value of 0.763, it means that maternal age, knowledge, and attitude collectively influence 76% of the occurrence of high-risk pregnancy in pregnant women, while the remaining 23.7% (100-76.3) is influenced by other variables not examined in this study.